The Therapeutic Efficacy and Safety of Compound Kushen Injection Combined with Transarterial Chemoembolization in Unresectable Hepatocellular Carcinoma: An Update Systematic Review and Meta-Analysis - Ma, Xiao; Li, Rui-Sheng; Wang, Jian; Huang, Yin-Qiu; Li, Peng-Yan; Wang, Ji; Su, Hai-Bin; Wang, Rui-Lin; Zhang, Ya-Ming; Liu, Hong-Hong; Zhang, Cong-En; Ma, Zhi-Jie; et al. (Frontiers in Pharmacology, 2016)
Background: Compound Kushen Injection (CKI) is a Chinese patent medicine approved by the Chinese State Food and Drug Administration for the treatment of various types of solid tumors. CKI, combined with transarterial chemoembolization (TACE), is believed to increase the therapeutic efficacy of unresectable hepatocellular carcinoma (HCC). We report an updated and extended meta-analysis with detailed outcomes of both the efficacy and adverse events of CKI combined with TACE therapy. Materials and methods: Electronic databases, including PubMed, Embase, the Cochrane Library, the Chinese Biomedical Database (CBM), Wanfang, the VIP medicine information system (VMIS) and the China National Knowledge Infrastructure (CNKI), were examined for relevant articles before November 13, 2015. An odds ratio (OR) was used to estimate tumor response, Karnofsky Performance Scale (KPS) improvement, Child-Pugh improvement, survival rate and adverse events. A publication bias and a subgroup analysis were also assessed. Results: Eighteen studies, with a total of 1,338 HCC patients who met the criteria for the meta-analysis, were included. Tumor response, KPS improvement and Child-Pugh improvement were significantly enhanced for the combination therapy compared to TACE alone (OR=1.84, 95% CI: [1.46, 2.33], P<0.00001; OR=2.37, 95% CI: [1.76, 3.18], P<0.00001; OR=1.81, 95% CI: [1.08, 3.03], P=0.02, respectively). The combination therapy was associated with an improvement in one-year and two-year survival rates but not an improved three-year survival rate (OR=2.40; 95% CI: [1.59, 3.62], P<0.0001; OR=2.49, 95% CI: [1.24, 5.00], P=0.01; OR=2.49, 95% CI: [0.94, 6.61], P=0.07, respectively). A safety analysis indicated that adverse events (including nausea/vomiting, fever, hepatalgia, increased transaminase, increased bilirubin and leukopenia) were reduced for the combination treatment compared to TACE alone. Conclusion: The combination treatment of TACE and CKI was associated with improved tumor response, KPS and Child-Pugh improvement and improved one- and two-year survival rates in patients with unresectable HCC. The three-year survival rate was not improved. The combination therapy resulted in a reduction in adverse events. The findings of this study should be interpreted with caution because of the small sample size and study limitations.